2016
DOI: 10.1177/0733464815577139
|View full text |Cite
|
Sign up to set email alerts
|

Dying With Carolyn

Abstract: This article examines the development, implementation, and evaluation of a pilot project utilizing high-fidelity simulation (HFS) to improve frontline staff members' confidence and skills to communicate about death and dying in long-term care homes. The target group was unregulated care providers who provide palliative care for residents and their families. Eighteen participants engaged in the educational intervention and evaluation. Results supported the effectiveness of HFS as an educational tool for unregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This indicates the need for quality improvement because early discussion of goals of care is a best practice in providing EOLC to elderly people with serious illness [91, 92]. The overall QPC-LTC research identified that most LTC staff were not comfortable having advance care planning and EOL conversations with residents and families [27, 28, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…This indicates the need for quality improvement because early discussion of goals of care is a best practice in providing EOLC to elderly people with serious illness [91, 92]. The overall QPC-LTC research identified that most LTC staff were not comfortable having advance care planning and EOL conversations with residents and families [27, 28, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…In the last 20 years, simulation has evolved remarkably. High-fidelity simulation allows the re-enactment of real situations that include procedures with communication skills, making it a training strategy that facilitates EOL education for health professionals and students [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Based on personal experience and the relevant nursing literature, opportunities to reflect on and converse about death is necessary, especially for students who have not yet had experiences in actual healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…UCPs provide up to 80% of direct care to older adults, yet they are an understudied and underrepresented workforce in the literature (Ginsburg et al, 2016;Kortes-Miller, Jones-Bonofiglio, Hendrickson, & Kelley, 2015). UCPs have different job titles such as healthcare aides, nurses' aides, personal support workers or nursing assistants.…”
Section: Introductionmentioning
confidence: 99%
“…Case study Residential long-term-care -Lack of collaboration between personal support workers (PSWs) and social workers or other members of the team -PSWs may require more education and training to gain cultural competency which has potential to improve quality of care (Johnson & Noel, 2007) and providing emotional support to patients (Berta et al, 2013;Giosa, Holyoke, Bender, Tudge, & Gifford, 2015;Kortes-Miller et al, 2015;Waskiewich, Funk, & Stajduhar, 2012). According to Guay et al (2013) (Vincent et al, 2016), health promotion (Johnson & Noel, 2007), therapeutic recreational programmes (Sullivan & Sharpe, 2005), physical mobility (Slaughter & Estabrooks, 2013) and palliative care (Kaasalainen, Brazil, & Kelley, 2014).…”
mentioning
confidence: 99%